ARCTIC Surviving Sources of the Classical Geographers Through Late Antiquity and the Medieval Period PIERGIORGIO PARRONI* - The Pennsylvania State University CiteSeerX Archives
The canonical texts through which Greek geographical know-ledge passed into the Latin world belong to the first century A.D.: they are the Chorography of Pomponius Mela ’ and the geography books (3-6) of Pliny the Elder’s Natural History. Neither Mela nor Pliny can be called geographers in the modern sense of the term, for their geography was acquired from books and destined for school use or to satisfy the en-cyclopedic curiosity of the erudite. This conception of geo-graphy lasted a very long time. It was only much later, begin-ning in the ninth century, that a new conception of geography developed, based not only on the classical tradition, but also on accounts of voyages rich in elements of fantasy, and on the direct experience of the narrator which, again, was not always free of marvels and the supernatural. The aim in this paper is to follow the evolution of this thread of classical geography